The effectiveness of topical vitamin D3 for dry skin in elderly - Nafaisa, He Yeon Asva; Waskito, Fajar; Martien, Rony; Danarti, Retno (Indonesian Journal of Biomedicine and Clinical Sciences, 2024)
Dry skin is one of the most common dermatoses found in the elderly. Vitamin D is an essential fat-soluble vitamin that has a role in repairing the skin barrier. Topical administration of vitamin D3 is expected to increase skin hydration in the elderly. Thirty-two participants were divided into two groups, namely 5000 IU vitamin D3 and the base lotion groups. The assessment was carried out by calculating the overall dry skin score (ODS), transepidermal water loss (TEWL), and skin capacitance every 4 wk for 12 wk. All groups showed an improvement in ODS, a decrease in TEWL, and an increase in skin capacitance value at the end of the measurement, and no significant side effects were reported. The 5000 IU vitamin D3 lotion group had the highest level of skin hydration compared to the other group (p>0,05). We conclude that the administration of 5000 IU vitamin D3 lotion may be administrated safely and improve skin hydration in the elderly but is not more effective than base lotion.